Marketing Strategy Planning for Mangga Keuken Production House - Nataprawira, Achmad Baehaki; Saphiranti, Dona (The Indonesian Journal of Business Administration, 2013)
Micro, Small and Medium Enterprises in many industrialized countries such as Japan and the United States of America proved to be a strong pillar in the national macro economy. The role or contribution of SMEs in economies is large enough, especially in providing employment. Bandung city has now been referred to as Indonesia's city of creative industry because of the creative ideas from his indie music, clothing distribution to the culinary industry. One of the creative industries rapidly growing is culinary industry. Culinary business is a business opportunity that will never die because people need food to live. Mangga Keuken is a brand that researchers have engaged in the culinary industry, as businesses started by necessity, a hobby and as a connoisseur of the culinary itself. Mangga Keuken stood at the end of 2012. In a mid a very dynamic culinary trend Mangga Keuken offers products with the concept that refers to the original taste. Departing from the idea of the concept, the product of Mangga Keuken specialized in: cookies, pastries and cakes.The objective of this study is to formulate Mangga Keuken’s marketing strategy to increase consumer’s trust in its product, as well as the methods and the right system reform in the face of competition in the market at present and in the future.The research method used in this research is descriptive analysis method with a case study approach conducted to describe the situation that occurred in the business world that moves at a culinary business with Mangga Keuken as its main object. Object under study is the situation of the business environment externally and internally used as a basis for analyzing marketing strategies to increase sales. Quantitative and qualitative approach done by surveys that requesting information from respondents selected as a sample to represent the entire population using a questionnaire with individual unit of analysis.The result of this study is the business solutions in accordance with the resources owned by the company at this time is to establish cooperation (Partnership) so as to have the distribution channels to market their products to a wider market and register the company and its products to the legal entity so that consumers and potential consumers have more faith in products of Mangga Keuken. To be known by the customers, Mangga Keuken should have a unique packaging and display at the store must be interesting for costumer, so they will be attracted to come to the booth and when the try the product, they’ll love the product and then buy it. To reach the outside customer, Mangga Keuken can use twitter, facebook, instagram or other social media. Key Words: Production House, Mangga Keuken, Marketing Strategy, Partnership